Health-promoting lifestyle and quality of life in affected and unaffected menopausal women by primary osteoporosis - Somayeh Abdolalipour; Mojgan Mirghafourvand; Nafiseh Ghassab-Abdollahi; Azizeh Farshbaf-Khalili (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Primary osteoporosis is a common complication of aging and menopause. The negative effects of osteoporosis in the coming years will increase by increasing life expectancy and population aging. The purpose of this research was to compare health-promoting lifestyle and quality of life in postmenopausal women with and without primary osteoporosis. MATERIALS AND METHODS: This cross-sectional analytical research was conducted on 445 postmenopausal women aged 50-65 selected by simple random sampling in Tabriz health centers from September 2018 to July 2019. Data collection instruments included demographic, midwifery, anthropometric, health-promoting lifestyle profile II and menopausal quality-of-life questionnaire questionnaires, and serum test checklist (25-hydroxy vitamin D, complete blood count/diff, thyroid-stimulating hormone, fasting blood sugar, Calcium, and Phosphor). Dual-energy X-ray absorptiometry method was used to measure bone density. Data were analyzed using SPSS/23 through descriptive and inferential statistics such as Chi-square, independent t-test, Mann-Whitney, and multiple regression. RESULTS: The mean score of lifestyle was 141.2 ± 21.9 in normal and 127.2 ± 25.4 in osteoporosis group, and differences were statistically significant in total score (P < 0.001) and all subdomains. The mean score of quality of life was 3.9 ± 1.2 in the normal and 4.5 ± 1.4 in the osteoporotic group. The differences were significant in total score (P < 0.001) and all subdomains except for sexual function subdomain (P = 0.064). Logistic regression adjusted for confounders indicated by one unit increase in total lifestyle score, the odds of primary osteoporosis reduced by 2.2% (adjusted odds ratio [0.95% confidence interval]: 0.978 [0.963-0.994], P = 0.006). CONCLUSION: To prevent of primary osteoporosis and improve the quality of life of postmenopausal women, it seems that education and implementation of health-promoting lifestyle are essential. The research findings can be used to plan for health care in middle and old ages.